GE_GERICHTE C/28648/2010 vom 12. März 2013 - GE Cour de justice (2013)
DIVORCE; CONDUITE DU PROCÈS; VOIE DE DROIT; CONDITION DE RECEVABILITÉ; SECOND ÉCHANGE D'ÉCRITURES; DOMMAGE IRRÉPARABLE ; SÛRETÉS | aRTGMC.24; aRTGMC.25.3.1; CPC.319.b.2